Observer-less Fixed-Time Speed Control For Permanent Magnet Synchronous Motors with matched-mismatched disturbances - Cholahan, Varin; Wongvanich, Napasool; Tangsrirat, Worapong (My University, 2025)
This paper presents a state-dependent Variable Exponent Coefficient Sliding Mode Control (VECFSMC) By inducing fixed-time stability analysis, the proposed state-dependent sliding surface provides not only system stability but also a quick response in a fixed period of time as well as counteract with matched and mismatched disturbances. The proposed sliding mode control strategy does not use observers to estimate the disturbances. The designed sliding mode surface possesses robustness properties which is sufficient to cope with both matched and mismatch disturbances in a period of fixed time. Firstly, the mathematical model of permanent magnet synchronous motor and the mathematical background of variable exponent coefficient are demonstrated theoretically. Secondly, the state-dependent sliding surface with variable exponent coefficient is designed. The controller that can manipulate both the speed of PMSM and matched-mismatched disturbances is constructed. Lyapunov function is applied to assess the stability of the proposed method. Finally, a numerical simulation with PMSM drive shows fast convergence, good robustness against both matched and mismatched disturbances. The proposed fixed-time controller with this observer-less method offers high efficiency and offers not too complicated control solution comparing to the other fixed-time and finite-time methods with a small number of parameters.
Keywords: fixed-time state-dependent sliding mode control (FTSMC); matched disturbances; mismatched disturbances; nonlinear control; observer-less; permanent magnet synchronous motor (PMSM)